Associations between community-based aged care services and subjective well-being among older adults in China: the mediating roles of self-rated and mental health - Ya Wang; Xiaojing Bai; Haitang Zhao (PLoS ONE, 2026)
Background Against the backdrop of accelerating population aging worldwide, promoting well-being among older populations has emerged as a critical objective for achieving healthy aging. Community-based aged care services (CACS) represent a key strategy to complement informal kinship-based support and strengthen the comprehensive old-age welfare system. Methods This study utilized cross-sectional data from the nationally representative 2018 Chinese Longitudinal Healthy Longevity Survey (CLHLS) to explore the relationship between the availability of CACS and the subjective well-being of older adults. We employed an ordinary least squares (OLS) regression model to examine this association, followed by a Bootstrap mediation analysis to test the potential mediating roles of self-rated health and mental health. Results The empirical findings indicate that a greater availability of CACS is significantly associated with higher levels of subjective well-being among older adults, and this association varied by gender, age, region, and the specific type of CACS service utilized. Furthermore, self-rated health and mental health were identified as significant mediators in the relationship between CACS availability and subjective well-being. Conclusion The study concludes that the availability of CACS is positively linked to the subjective well-being of older adults, partly through better self-rated health and mental health. These findings suggest that with the support of CACS, older adults may be better equipped to adapt to the aging process and maintain a positive outlook on life.